The Brief Accessibility, Responsiveness, and Engagement Scale: A Tool for Measuring Attachment Behaviors in Clinical Couples. (8th January 2016) - Sandberg, Jonathan G.; Novak, Joshua R.; Davis, Stephanie Y.; Busby, Dean M.
Abstract : Measuring attachment behaviors is relevant to creating secure couple relationships. This article seeks to test and examine the reliability and validity of the Brief Accessibility, Responsiveness, and Engagement (BARE) Scale—a practical measure of couple attachment–in a clinical sample. Couples took the BARE and other assessments measuring relationship functioning (self and partner reports of relationship satisfaction, relationship stability, positive and negative communication, and attachment styles). Results suggest that the BARE appears to be a reliable and valid tool for assessing couple attachment and can accurately predict and classify whether the couples belong in the clinical or nonclinical group, as well as their level of relationship satisfaction. Results also indicate attachment behaviors are related to relationship outcomes.